Nucleation, reorganization and disassembly of an active network from lactose-modified chitosan mimicking biological matrices. (15th March 2019) - Furlani, Franco; Sacco, Pasquale; Scognamiglio, Francesca; Asaro, Fioretta; Travan, Andrea; Borgogna, Massimiliano; Marsich, Eleonora; Cok, Michela; Paoletti, Sergio; Donati, Ivan
Graphical abstract: Highlights: Boric acid causes the formation of transient network in lactose-modified chitosan. The active network shows strain-hardening features resembling ECM components. The super-soft material can reorganize and undergo disassembly. Abstract: Developing synthetic materials able to mimic micro- and macrorheological properties of natural networks opens up to novel applications and concepts in materials science. The present contribution describes an active network based on a semi-synthetic polymer, a lactitol-bearing chitosan derivative (Chitlac), and a transient inorganic cross-linker, boric acid. Due to the many and diverse anchoring points for boric acid on the flanking groups of Chitlac, the cross-links constantly break and reform in a highly dynamic fashion. The consequence is a network with unusual non-equilibrium and mechanical properties closely resembling the rheological behavior of natural three-dimensional arrangements and of cytoskeleton. Concepts like network nucleation, reorganization and disassembly are declined in terms of amount of the cross-linker, which acts as a putative motor for remodeling of the network upon application of energy. The out-of-equilibrium and non-linear behavior render the semi-synthetic system of great interest for tissue engineering and for developing in-vitro mimics of natural active matrices.